(3fXGe GdJTZjd ddceHjhJQ GdTNUj (BMS-dos & PS-dos /s - (3GSGeI eMeO GdMSjfjs ((3HjQhJ (B:s (3OGQ GdQGJH GdLGeYjI,s)
(3GdeYdheGJ GdCSGSjI Yf GdceHjhJQ(B.s
Keywords: (3eGjcQhShaJ OhS (B((3eda MGShH(B)s; (3fXe GdJTZjd (B((3MGSHGJ EdcJQhfjI(B)s